PENGARUH DER, CR, DAN ROA TERHADAP PBV PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA PERIODE 2021–2024 - Ninik Dwi Atmini; I'anatus Sholikhah (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to examine the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) on Price to Book Value (PBV) in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. A quantitative approach with causal design was employed. The population comprised 98 companies, and 36 companies were selected as samples through purposive sampling, yielding 144 total observations. Data were sourced from annual reports published at www.idx.co.id and analysed using multiple linear regression via SPSS. The results show that: (1) DER has a positive and significant effect on PBV (t = 2.100; sig. 0.020); (2) CR has a positive and significant effect on PBV (t = 2.507; sig. 0.013); (3) ROA has a positive and significant effect on PBV (t = 7.541; sig. 0.000); and (4) simultaneously, DER, CR, and ROA significantly affect PBV (F = 19.825; sig. 0.000). The Adjusted R Square of 0.683 indicates that the three variables explain 68.3% of the variation in PBV.